충주호 상류 대농갱이(Leiocassis ussuriensis)의 연령과 성장 - 안정은; 김창수; 신수정; 황산; 김두호; 이상우; 류동기; 최종덕; An Jung Eun; Kim Chang Su; Shin Su Jeong; Hwang San; et al. (한국해양생명과학회지, 2025)
The age and growth of Ussurian Bullhead, Leiocassis ussuriensis sampled in the Upper Reaches of Lake Chungju were determined from 274 vertebrae from March 2024 to December 2024. Age of L. ussuriensis was determined from the rings on the vertebra. As a result of this study, vertebrae were suitable as age characters. In vertebrae, the annual rings are formed once a year at April. The spawning season is from May to July, and it takes 10 months (0.83 years) for the formation of the first ring. For vertebrae, there was no difference in the growth equation of females and males for the total length (p>0.05). The von Bertalanffy growth equation, estimated based on the total length (TL), was Lt=532.94(1-e-0.240(t+0.647)) for the vertebrae. 2024년 3월부터 2024년 12월까지 충주호 상류에서 채집된 대농갱이(Leiocassis ussuriensis) 274개체의 척추골을 이용하여 연령과 성장을 분석하였다. 대농갱이의 연령은 척추골에 형성된 윤문을 통해 결정하였다. 본연구 결과 척추골은 연령 측정에 적합한 자료로 판단되었다. 척추골에는 매년 4월에 1회성 장륜이 형성되었으며, 산란기는 5월부터 7월, 초륜은약 10개월(0.83년) 이지 난 시점에 형성되었다. 척추골을 기준으로 분석한 결과, 암컷과 수컷 간의 전장의 성장에는 유의한 차이가 없었다(p) 0.05) 척추골을 기준으로 전장(TL)에 대해 추정된 von Bertalanffy 성장식은 다음과 같다: Lt=532.94(1-e-0.240(t+0.647)).